2016
DOI: 10.1016/j.cbpc.2015.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of tenerplasminin-1, a serine peptidase inhibitor with antiplasmin activity from the coral snake ( Micrurus tener tener ) venom

Abstract: A plasmin inhibitor, named tenerplasminin-1 (TP1), was isolated from Micrurus tener tener (Mtt) venom. It showed a molecular mass of 6542 Da, similarly to Kunitz-type serine peptidase inhibitors. The amidolytic activity of plasmin (0.5 nM) on synthetic substrate S-2251 was inhibited by 91% following the incubation with TP1 (1 nM). Aprotinin (2 nM) used as the positive control of inhibition, reduced the plasmin amidolytic activity by 71%. Plasmin fibrinolytic activity (0.05 nM) was inhibited by 67% following in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…It is a slow and tight binding inhibitor of plasmin. The peptide (TP1) isolated from Micrurus tener tener venom is also an inhibitor of plasmin [ 39 , 121 , 122 ]. TP1 has a molecular mass similar to Kunitz-type peptides, but its sequence is not reported till now.…”
Section: Snake Venom Peptides and Their Potential Pharmacological mentioning
confidence: 99%
See 1 more Smart Citation
“…It is a slow and tight binding inhibitor of plasmin. The peptide (TP1) isolated from Micrurus tener tener venom is also an inhibitor of plasmin [ 39 , 121 , 122 ]. TP1 has a molecular mass similar to Kunitz-type peptides, but its sequence is not reported till now.…”
Section: Snake Venom Peptides and Their Potential Pharmacological mentioning
confidence: 99%
“…The peptide and its complex also inhibited the fibrinogen-clotting activity of thrombin. Another Kunitz-type inhibitor (namely PIVL) isolated from Macrovipera lebetina venom, displayed potent anti-tumor activity through interference with integrin receptor function [ 26 , 122 , 123 , 124 , 125 ].…”
Section: Snake Venom Peptides and Their Potential Pharmacological mentioning
confidence: 99%
“…The simultaneous release of pro-inflammatory mediators, such as TNF-α, may promote PAI-1 expression, thus inhibiting this activity (Levi and van der Poll, 2017;Petäjä, 2011). In addition, the low pro-fibrinolytic activity may be associated with tenerplasminin-1, a serine protease inhibitor isolated from Mtt venom that decreases the activity of plasmin and delays clot lysis induced by tPA (Vivas et al, 2016). Since binding to cell receptors confers protection to plasminogen activators from PAI-1 inhibition (Li et al, 2007), our next approach was evaluating pro-fibrinolytic activity on the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…Micrurus envenomation is characterized by neurotoxic symptoms and may lead to death from muscle paralysis and respiratory arrest. Some reports have shown that these venoms may also contain hemorrhagic, hemostatic, hemolytic and edematogenic activities (Barros et al, 1994;Casais-e-Silva and Teixeira, 2017;Salazar et al, 2011Salazar et al, , 2018Tambourgi et al, 1994;Vivas et al, 2016). In the United States, only two species are responsible for all coral snake toxicity, Micrurus fulvius fulvius (Eastern coral snake) and Micrurus tener tener (Texas coral snake), and most of the information available rely on the Eastern coral snakebites.…”
Section: Introductionmentioning
confidence: 99%
“…Cerestes cerestes antivenom and Macrovipera mauritanica antivenom cross react with Bitis arietans antivenom due to presence of antigens common to them [31]. Tenerplasminin-1 (TP 1 ), a plasmin inhibitor isolated from Micrurus tener tener venom was similar to Kunitztype serine peptidase inhibitors [32]. Rauwolfia serpentina inhibits Daboia russelii venom [33].…”
Section: Treatment Of Snake Envenomationsmentioning
confidence: 99%